2016
DOI: 10.1002/mbo3.373
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the mechanisms of action of human secretory RNase 3 and RNase 7 against Candida albicans

Abstract: Human antimicrobial RNases, which belong to the vertebrate RNase A superfamily and are secreted upon infection, display a wide spectrum of antipathogen activities. In this work, we examined the antifungal activity of the eosinophil RNase 3 and the skin‐derived RNase 7, two proteins expressed by innate cell types that are directly involved in the host defense against fungal infection. Candida albicans has been selected as a suitable working model for testing RNase activities toward a eukaryotic pathogen. We exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 95 publications
5
38
0
Order By: Relevance
“…The potential contribution of the protein catalytic activity was blocked by assaying the activity of the RNase 3 H15A variant, in which one of the two catalytic His residues is replaced. Previous work in our laboratory already confirmed that the H15A mutant was an appropriate construct to test the effect of total removal of the RNase enzymatic activity without alteration of the protein's three-dimensional structure (PDB ID 4OWZ) (24). The present results corroborate that the active site-defective mutant achieves an antibiofilm activity equivalent to that of the wild-type protein (Fig.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The potential contribution of the protein catalytic activity was blocked by assaying the activity of the RNase 3 H15A variant, in which one of the two catalytic His residues is replaced. Previous work in our laboratory already confirmed that the H15A mutant was an appropriate construct to test the effect of total removal of the RNase enzymatic activity without alteration of the protein's three-dimensional structure (PDB ID 4OWZ) (24). The present results corroborate that the active site-defective mutant achieves an antibiofilm activity equivalent to that of the wild-type protein (Fig.…”
Section: Discussionsupporting
confidence: 86%
“…Human RNase 3, also known as the eosinophil cationic protein (ECP), is a small, highly cationic protein (pI ϳ11) that is stored in the secondary granules of eosinophils (19,20). RNase 3 is secreted during the infection process, where the protein exerts high antimicrobial activity against a wide range of microorganisms, such as bacteria, yeast, viruses, and parasites (18,(21)(22)(23)(24). Moreover, our laboratory has reported RNase 3's high affinity with negatively charged lipopolysaccharides (LPS) from Gram-negative bacteria outer membranes (25), a feature that mediates the protein's high bacterial agglutination ability (26).…”
mentioning
confidence: 99%
“…RNase7 is secreted by a variety of epithelial cells (Table 2 ) and mostly contributes to urinary tract sterility and epidermis protection ( 43 , 80 82 ). Together with high antimicrobial activity against a variety of infective microorganisms ( 82 , 87 , 89 , 193 ), some immuno-modulatory properties were reported. RNase7 expression is upregulated during kidney infection ( 84 ).…”
Section: The Rnase a Superfamilymentioning
confidence: 99%
“…Although the catalytic activity of the protein was reduced, the antibacterial activity was maintained and increased After immobilization on MNP. Recent studies have demonstrated that indeed, the antimicrobial and catalytic activities appear unrelated [16,86]. Finally, it should be noted that the obtained nanobioconjugates were prepared at a single RNases:MNPs ratio, as detailed in the Materials and Methods section.…”
Section: Discussionmentioning
confidence: 99%